Accurate detection of spread-spectrum modulated signals in reverberant underwater environments. (February 2015) - Aparicio, Joaquín; Jiménez, Ana; Álvarez, Fernando J.; Ureña, Jesús; De Marziani, Carlos; de Diego, Daniel; Cruz, Nuno; Campos, Helder
Highlights: Accurate detection of coded acoustic signals are tested in two real scenarios. These environments are underwater channels highly affected by multipath. A developed underwater acoustic propagation model is used to compare the results. The propagation model could be used to predict signal detection in other channels. Abstract: In those positioning systems based on the detection of acoustic signals, an accurate detection of the arrival times is crucial for a correct estimation of the distance between nodes, and therefore, for the precise estimation of the node that wants to be located. In order to obtain this arrival time more accurately, acoustic signals can be coded using pseudorandom noise, but these coded signals are still affected by underwater channel phenomena. In this work, the detection of spread-spectrum modulated signals is analyzed in underwater environments that are highly affected by multipath and reverberation. A spread-spectrum signal, which consist of a modulated Kasami code, has been emitted through two different pools, reaching a receiver where it has been captured after following several line-of-sight and non-line-of-sight paths. Then, a correlation process has been performed offline to provide information about the arrival times (times-of-flight) that form the multipath structure. These times-of-flight are compared with those provided by an underwater acoustic propagation model, in order to test the performance of this model and its capacity to predict the outcome of signal detection in underwater environments with a strong multipath and reverberation component. That way, the validated propagation model could be later used in future studies to predict the detection of spread-spectrum signals and the performance of systems that use them in these adverse environments.